Application of The SQ3R Method to Improve The Effective Reading Skills Of PGSD Students in Understanding Scientific Articles - Wahyuningsih, Ika; Sabarudin; Biya Ebi Praheto (Abjad Journal of Humanities & Education, 2025)
This study aims to explore the effectiveness of the SQ3R (Survey, Question, Read, Recite, Review) method in improving the effective reading skills of Elementary School Teacher Education (PGSD) students in understanding scientific articles. Using a qualitative descriptive approach, this study involved 25 students in the fourth semester of PGSD at Sarjanawiyata Tamansiswa University as subjects. Data collection is carried out through observation, interviews, and documentation studies, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the SQ3R method is implemented according to the stages to understand scientific articles and has positive implications for improving effective reading skills, especially through the Survey and Question stages that build a focused and critical reading orientation. However, there are still obstacles at the Read, Recite, and Review stages related to the absorption and articulation of information orally. Students responded positively to this method, although pedagogical assistance was still needed to optimize its implementation, especially in strengthening academic communication.